Indeks Literasi Digital Muslim Milenial di Indonesia - Raharjo, Novianto Puji; Rozi, Bahru; Burhani , Roisul; Raya, Moch. Khafidz Fuad (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
This article reports on a quantitative explanatory research conducted with nationwide survey 1000 of millennial Muslim generations in five major cities in Indonesia regarding the digital literacy. The results have found that the level of millennial Muslim’s digital literacy in Indonesia is quite good. Although the majority learn the internet independently, they denote quick response in adapting to cyber culture. Unfortunately, the duration of internet access has remained high that is likely to open up opportunities for negative effects of the internet. In addition, this study argues that several generations of millennial Muslims unwittingly have contributed to spreading hoax because they mostly do not check or validate information to authoritative sources.